Change in salivary levels of chromogranin A in children by hearing dental air turbine noise - Okano Akiko; Miyamoto Yoichi; Asari Jin; Kamijo Ryutaro; Inoue Mitsuko (Pediatric Dental Journal, 2009)
Dental fear in children can be a psychological barrier for maintenance of oral health, thus it is important to objectively evaluate the responses to stress stimuli produced during dental treatments. In this study, we analyzed the stress responses of 15 preschool (3- to 6-year) and 22 school-aged (6- to 12-year) children to dental air turbine noise by measuring salivary levels of chromogranin A (CgA), a marker of psychological stress. Salivary CgA was significantly increased during exposure to the noise in the school-aged subjects, especially in those who had previously experienced tooth excavation, while there was no significant difference in CgA levels before and during noise exposure in those without such experience. In the preschool children, the noise did not induce increased secretion of CgA even in those with previous excavation experience. In addition, the levels of dental fear were assessed using a dental subscale of children’s fear survey schedule (CFSS-DS), while reactions during dental care were scored according to the Frankl Behavior Rating scale. In the school-aged children, change in salivary CgA level was not correlated with CFSS-DS (r = 0), while there was a weak negative correlation with Frankl score (r = -0.202). Our results indicate that air turbine noise causes psychological stress in school-aged children, especially in those who have previously received dental treatments.